Business Fleets and EVs: Taxation changes to support home charging from the grid, and affordability. Fast track project for RACE for 2030. - Mortimore, Anna; Kraal, Dianne; Lee, Ki-Hoon; Klemm, Celine; Akimov, Alexandr (RACE for 2030 Ltd, 2022)
This project investigated how tax changes can accelerate the uptake of battery electric vehicles (BEVs) within business fleets by encouraging home charging. The project recommends 17 short-term and long-term tax changes that can accelerate the uptake of business fleet BEVs and encourage home charging